Is the Antiglobulin Test a Good Marker for Predicting the Development of Hemolytic Disease of the Newborn in ABO Incompatibility? - Aydin, Mustafa; Deveci, Ugur; Orman, Aysen; Taskin, Erdal (Elsevier Taiwan, 2016)
[Abstract Not Available]